A New Era in Diagnostic Ultrasound, Superb Microvascular Imaging: Preliminary Results in Pediatric Hepato-Gastrointestinal Disorders - Ohno, Yasuharu; Fujimoto, Tamotsu; Shibata, Yukari (European Journal of Pediatric Surgery, 2017)
Introduction Superb microvascular imaging is a new ultrasound image processing technique that uses advanced clutter suppression to extract flow signals from vessels and which helps us visualize very small vascular structures that were not previously visible without the use of a contrast agent. We herein analyzed the usefulness of superb microvascular imaging in the diagnosis of hepato-gastrointestinal disorders in pediatric patients.Materials and Methods Fifty-six pediatric patients who underwent a total of 81 superb microvascular imaging examinations with an Aplio 300 ultrasound system (Toshiba Medical Systems, Tokyo, Japan) were enrolled in this study. The subjects underwent conventional ultrasound examinations, including Doppler imaging followed by superb microvascular imaging. The superb microvascular imaging findings and standard imaging were compared. All of the examinations were performed without sedation.Results The average age of the patients (male, n = 38; female, n = 18) was 4 years. The clinical diagnoses included hepatobiliary disorders (n = 29), acute appendicitis (n = 10), and other intestinal disorders (n = 17). The target organs for superb microvascular imaging were the liver, appendix, rectum, intestine, gallbladder, and lymph node. In most of the patients, superb microvascular imaging achieved the excellent visualization of microvascular structures, revealing abnormal vasculature in 21 out of 46 (45.7%) examinations of the liver, 9/9 (100%) examinations of the appendix, 0/11 (0%) examinations of the rectum, 9/11 (81.8%) examinations of the intestine, 0/1 (0%) examinations of the gallbladder, and 3/3 (100%) examinations of the lymph nodes. Superb microvascular imaging was superior to Doppler imaging for depicting the microvascular structures.Conclusions Superb microvascular imaging is especially useful for depicting the microvascular flow and can aid in the diagnosis and treatment planning for pediatric patients with hepato-gastrointestinal disorders.
Keywords: superb microvascular imaging; ultrasound; pediatric; gastrointestinal